Physico-mechanical and decay resistance properties of chemically modified tropical wood material - Islam, M.S.; Hamdan, S.; Hasan, M.; Rusop, M.; Rahman, M.R.; Mohd Idrus, M.A.M (Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2012)
In this present research, several kinds of selected tropical light hardwoods were chemically modified with benzene diazonium salt to improve their physico-mechanical and decay resistance properties. Benzene diazonium salt underwent a coupling reaction with wood which was confirmed through fourier transform infrared spectroscopic analysis. The compressive modulus of the treated wood increased, whereas modulus of rupture was shown to decrease on treatment. Water absorption was also found to decrease considerably after modification. The modified wood samples had higher hardness (Shore D) value compared to that of the control ones. The wood was exposed to two types of fungi; white-rot (Polyporus versicolor) and brown-rot (Postia placenta), for 12 weeks and then decay was assessed through weight loss percentage (%). A significant improvement was found in the modified wood compared to the control wood.